HUBUNGAN ANTARA KONSEP DIRI DENGAN TINGKAT DEPRESI PENDERITA DIABETES MELLITUS DI RUMAH SAKIT UMUM UNGARAN - saraswati, rina (LPPM STIKES MUHAMMADIYAH GOMBONG, 2009)
Diabetic Mellitus (DM) is able to change the psychology of patient such as the changing of self concept and depression. Psychological stress can happen when someone accepts diagnosis of DM. they ought DM can give many problems such as Diet Controlling and long term complex and therapy. The purpose of this research is to know the relation between self concept and level of depression in Ungaran Public Hospital. The design used in this research was cross-sectional descriptive. The taking of samples used purposive sampling method, the number of sample is 37 persons. The data analysis was to know whether there is a correlation between variables using pearson product moment test. The result of this research using pearson product moment test showed that there was a relation (p value 0,000 < 0,05) between self consept and depression level of DM in Ungaran Public Hospital. During perform nursing hospital care, nurse need to know the worries of patient, the causes of self consept and depression disorder and to identify the coping that was used in handling the problems of self concept and depression of DM sufferer. Â Keywords: self concept, depression, Diabetic Mellitus